Killer summer [compact disc, unabridged] - Pearson, Ridley (Pearson, Ridley. Sun Valley, 2009)
The third installment of Pearson's Sun Valley series, Killer Summer takes us back to the high-stakes world of the wealthy and politically connected, just in time for the area's 17th Annual Wine Auction. The world's most elite wine connoisseurs have descended on Sun Valley to taste and bid on the world's best wines, including three bottles which are said to have been a gift from Thomas Jefferson to John Adams.